Kontroversi Implementasi Kebijakan Penenggelaman Kapal Dalam Rangka Pemberantasan Illegal Fishing di Indonesia - Chairun Nasirin; Dedy Hermawan (Universitas Sebelas Maret, 2017)
Illegal fishing in Indonesia have caused huge losses fisheries sector in order to realize the welfare of society. Ministry of Marine Affairs and Fisheries Republic of Indonesia take resolute policy to combat illegal fishing through drownings action actors of illegal fishing vessels. This study aims to analyze and discuss the sinking of the policy implementation actors of illegal fishing and environmental reactions arising from the policy. The method used literature study and documentation. This study shows that the sinking of the policy implementation by the Ministry of Marine Affairs and Fisheries Republic of Indonesia is a top-down models are characterized by regulatory certainty, a strong command system, instructional pattern and effective coordination, budget support, and the support of a strong bureaucracy. Implementation of this policy also has provoked harsh reaction to the policy environment in the form of protests from the countries of origin where the ships were sunk. Empirically, this research can help improve the implementation of policies to eradicate illegal fishing with sinking action, particularly on the management aspects of the reaction that the future policy environment can be more conducive and supportive policy implementation.